2003
DOI: 10.1001/archpsyc.60.6.572
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Levels of D-Serine in Patients With Schizophrenia

Abstract: Reduced levels of D-serine may play a role in the pathophysiology of schizophrenia, and serum D- and L-serine levels might provide a measurable biological marker for schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
128
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 462 publications
(143 citation statements)
references
References 24 publications
12
128
1
2
Order By: Relevance
“…116 Moreover, there is evidence that Dserine levels are reduced in the brain and blood of patients with schizophrenia. 117,118 Chumakov et al therefore speculated that the G72/DAO associations support the long-standing hypothesis of abnormal glutamatergic transmission in schizophrenia.…”
mentioning
confidence: 90%
“…116 Moreover, there is evidence that Dserine levels are reduced in the brain and blood of patients with schizophrenia. 117,118 Chumakov et al therefore speculated that the G72/DAO associations support the long-standing hypothesis of abnormal glutamatergic transmission in schizophrenia.…”
mentioning
confidence: 90%
“…10) In addition, we previously reported that the serum D-serine concentration was signiˆcantly reduced in patients with schizophrenia. 11) In 1998, Tsai et al reported that co-administration of D-serine with atypical antipsychotic drugs improved the symptoms of patients with schizophrenia. 12) Considering these reports together, DAAO inhibition by an exogenous drug could be eŠective for the treatment of schizophrenia.…”
mentioning
confidence: 99%
“…We have performed multiple molecular dynamics simulations ( N-Methyl-D-aspartate (NMDA) 4 receptors are ligand-gated ion channels that play a major role in learning and memory (1). They have also been implicated in a number of injury or disease states including for example, schizophrenia (2)(3)(4)(5). NMDA receptors are a distinct subtype of ionotropic glutamate receptor (6) in that they require both glutamate and glycine for activation and membrane depolarization (7).…”
mentioning
confidence: 99%